2008
DOI: 10.1002/ejoc.200800798
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and 13C NMR Spectroscopy of Model Compounds for the Microstructure Analysis of Poly(Vinyl Glycoside)s

Abstract: A series of glycosylated diol and triol derivatives was synthesized in order to serve as model compounds for the analysis of the stereochemistry, regiochemistry, and defect structures of poly(vinyl glycoside)s.13 C NMR spectroscopic analysis of these compounds revealed that the attached chiral carbohydrate substituents induced a strong correlation of the chemical shifts of both the anomeric C and the α-C atom of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The simplistic model (see Figure ), which prompted this study, was partly based on the idea that the remaining degrees of freedom of the MCPM group would be identical and hence the chirality would exhibit itself by reversing the relative positions of the two smallest groups, namely the methyl and the hydrogen. A previous study of chiral at the aglycone carbon of mannosides found this to be true with both isomers having the largest group anti . However, our recent study of the neutral mannosides with MCPM at the anomeric center found that the Ψ­(C-1–O-1–C­(MCPM)–C­(Cp) torsion angle had different minima .…”
Section: Resultsmentioning
confidence: 74%
“…The simplistic model (see Figure ), which prompted this study, was partly based on the idea that the remaining degrees of freedom of the MCPM group would be identical and hence the chirality would exhibit itself by reversing the relative positions of the two smallest groups, namely the methyl and the hydrogen. A previous study of chiral at the aglycone carbon of mannosides found this to be true with both isomers having the largest group anti . However, our recent study of the neutral mannosides with MCPM at the anomeric center found that the Ψ­(C-1–O-1–C­(MCPM)–C­(Cp) torsion angle had different minima .…”
Section: Resultsmentioning
confidence: 74%